Neuropharmacological Effects of Quercetin: A Literature-Based Review - Islam, Md. Shahazul; Quispe, Cristina; Hossain, Rajib; Islam, Muhammad Torequl; Al-Harrasi, Ahmed; Al-Rawahi, Ahmed; Martorell, Miquel; Mamurova, Assem; Seilkhan, Ainur; Altybaeva, Nazgul; Abdullayeva, Bagila; Docea, Anca Oana; et al. (Frontiers in Pharmacology, 2021)
Quercetin (QUR) is a natural bioactive flavonoid that has been lately very studied for its beneficial properties in many pathologies. Its neuroprotective effects have been demonstrated in many in vitro studies, as well as in vivo animal experiments and human trials. QUR protects the organism against neurotoxic chemicals and also can prevent the evolution and development of neuronal injury and neurodegeneration. The present work aimed to summarize the literature about the neuroprotective effect of QUR using known database sources. Besides, this review focuses on the assessment of the potential utilization of QUR as a complementary or alternative medicine for preventing and treating neurodegenerative diseases. An up‐to‐date search was conducted in PubMed, Science Direct and Google Scholar for published work dealing with the neuroprotective effects of QUR against neurotoxic chemicals or in neuronal injury, and in the treatment of neurodegenerative diseases. Findings suggest that QUR possess neuropharmacological protective effects in neurodegenerative brain disorders such as Alzheimer’s disease, Amyloid β peptide, Parkinson’s disease, Huntington's disease, multiple sclerosis, and amyotrophic lateral sclerosis. In summary, this review emphasizes the neuroprotective effects of QUR and its advantages in being used in complementary medicine for the prevention and treatment o of different neurodegenerative diseases.